Effects and feasibility of psychological interventions to reduce inattention symptoms in adults with ADHD: a systematic review. (2nd January 2023) - Scholz, Lisanne; Werle, Jana; Philipsen, Alexandra; Schulze, Marcel; Collonges, Julien; Gensichen, Jochen
Abstract: Background: Adult ADHD is common, highly comorbid, and restricts daily functioning. However, only a minority of patients receive appropriate treatment. Aims: Primary objective: To identify psychological interventions that diminish inattention symptoms in adults with ADHD. Secondary objective: To evaluate feasibility aspects. Methods: A search in PubMed, Cochrane Library, PsycInfo, PSYNDEX, and Eric was conducted. Interventions were grouped in: ADHD coaching, neuro feedback, cognitive training, psychoeducation, and behavioral therapy. Inattention symptoms were evaluated using standardized mean differences. Study quality was rated with the Cochrane Risk of Bias tool. Feasibility was assessed by number and time of sessions, setting, and qualification of the provider. Results: A total of N = 2229 results were identified, 19 randomized controlled studies were included in the analysis. Behavioral therapy showed effects on inattention symptoms [SMD: 0.44–1.71] when compared to inactive controls. In terms of feasibility, longer interventions did not outperform shorter ones and individual sessions were not superior to group sessions. No effects were given for neuro feedback, cognitive training, and psychoeducation in comparison to controls. Conclusion: For adults with ADHD behavioral therapy seems an effective intervention to reduce inattention symptoms. In terms of feasibility, brief interventions may be valuable for a primary care setting.